2011 Proceedings of the Thirteenth Workshop on Algorithm Engineering and Experiments (ALENEX) 2011
DOI: 10.1137/1.9781611972917.4
|View full text |Cite
|
Sign up to set email alerts
|

An Elimination Method for Solving Bivariate Polynomial Systems: Eliminating the Usual Drawbacks

Abstract: We present an exact and complete algorithm to isolate the real solutions of a zero-dimensional bivariate polynomial system. The proposed algorithm constitutes an elimination method which improves upon existing approaches in a number of points. First, the amount of purely symbolic operations is significantly reduced, that is, only resultant computation and square-free factorization is still needed. Second, our algorithm neither assumes generic position of the input system nor demands for any change of the coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…The problem of accurate root approximation is omnipresent in mathematical applications; certified methods are of particular importance in the context of computations with algebraic objects, e.g., when computing the topology of algebraic curves [10,6] or when solving systems of multivariate equations [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of accurate root approximation is omnipresent in mathematical applications; certified methods are of particular importance in the context of computations with algebraic objects, e.g., when computing the topology of algebraic curves [10,6] or when solving systems of multivariate equations [3].…”
Section: Introductionmentioning
confidence: 99%
“…tal comparisons in the context of [3] have shown that the approximate version of QIR gives significantly better running times than its exact counterpart. These observations underline the practical relevance of our approximate version and suggest a practical comparison with state-of-the-art solvers mentioned above as further work.…”
Section: Introductionmentioning
confidence: 99%
“…Then, for each distinct x * an eigenproblem of size equal to the dimension of its kernel should be solved. Another approach is to eliminate both x and y separately and then for each pair of projected coordinates check whether it constitutes a solution of the given system or not [8,14,44]. For many applications, a nontrivial final task is to determine which of the solutions are real.…”
Section: Notation and Preliminariesmentioning
confidence: 99%
“…For a fair comparison, each algorithm Table 3.2 Properties of the initial moderate-degree problem set, containing a total of 16 systems. All of these systems with the exception of lebesgue were taken from [8].…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…A GPU implementation of a bivariate solver over the real numbers is reported in [3]. Solving polynomial systems is a driving subject in symbolic computation with many successful results from theoretical to practical aspects.…”
Section: Introductionmentioning
confidence: 99%